Comparison of intralesional triamcinolone aceronide injection and incision curretage in resolution of primary chalazia in a tertiary care centre - Rahman, Hizbur (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Objective: To compare effectiveness of intralesional triamcinolone acetonide injection and incision curettage in the resolution of primary chalazia. Materials and methods: 250 diagnosed cases of primary chalazia were included in the study. For Comparative effectiveness of treatment modalities, about 125 cases were assigned each into group randomly. Group A were treated with incision and curettage while group B were treated with intralesional injection of triamcinolone acetonide. Followup was for 2 weeks after the procedures to see the resolution of the lesion. Treatment was considered successful if resolution was achieved in the lesion. Resolution was considered to be achieved if the lesion had regressed and there was normal function and appearance of the eyelid. Results: 250 cases of chalazion were included in the study. Age ranged from 20-60 years, with mean 40.33 ± 11.18 SD years. Group A and B were randomized. In Group A, about 57(45.6%) cases were in age range of 20-40 years, while remaining 68 (54.4%) cases were in age range of 41-60 years. In group B, about 53(42.4%) cases were in age range of 20-40 years, while the remaining 72(57.6%) cases were in age range of 41-60 years. In group A, about 74(59.2%) cases were males, while in group B, about 81 (64.8%) cases were males. Successful resolution was achieved by about 91(72.8%) cases in Group-A, and 73(58.4%) cases in Group B. p-value was calculated as 0.015. Conclusion: Incision curettage is more effective than intralesional triamcinolone acetonide injection in the treatment of primary chalazia.